THE EFFECT OF STRIVE ENABLENESS SOCIETY THROUGH THE ACTIVITY OF GARBAGE BANK TOWARD HEALTHY AND CLEAN LIFE BEHAVIOR PROGRAM EFFICACY - Arumawati, Dhani Setya; Astuti, fitri Budi (JURNAL ILMU KEPERAWATAN INDONESIA (JIKI), 2016)
..